'I can coexist with HIV': a qualitative study of perceptions of HIV cure among people living with HIV in Guangzhou, China - Qingyan Ma; Feng Wu; Gail Henderson; Stuart Rennie; Zachary C. Rich; Yu Cheng; Fengyu Hu; Weiping Cai; Joseph D. Tucker (Elsevier, 2016)
Little is known about perceptions of HIV cure among people living with HIV (PLHIV), despite them being crucial stakeholders in ongoing HIV cure research. A qualitative research study was conducted in Guangzhou, China, to explore the perceptions of HIV cure among PLHIV in relation to their views on HIV treatment, stigma and social identity. We conducted in-depth interviews with 22 PLHIV from September 2014 to June 2015. Our qualitative data revealed three major themes: (1) Representations of HIV cure: PLHIV generally thought HIV cure was distant from them; (2) Possibility of HIV cure: ideas about the possibility of HIV cure ranged from optimism to scepticism and pessimism; and (3) Life without HIV cure: some participants had adjusted well to the chronic condition of HIV and ART adherence. Although some PLHIV looked forward to HIV being cured, most of the PLHIV in our study had little interest in it. On the contrary, many felt it is more important and realistic to have access to better ART medication and more education for the general public to decrease HIV stigma today rather than develop a cure for tomorrow.